2008
DOI: 10.1631/jzus.b0820181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary conjugated linoleic acid on growth, fatty acid composition and hepatic lipogenesis in large yellow croaker (Pseudosciaena crocea R.)

Abstract: Zhao et al. / J Zhejiang Univ Sci B 2008 9(9)Abstract: We examined the effects of conjugated linoleic acid (CLA) on growth, fatty acid composition and enzyme activity of fatty acid oxidation in the liver of large yellow croaker. We divided 1600 fish (average initial weight 150 g) into 4 groups and reared them in 8 cages. Four dietary treatments were formulated to contain 0%, 1%, 2% and 4% (w/w) CLA, respectively. The fish were fed for 10 weeks ad libitum twice daily. We found that the dietary CLA had no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…) and large yellow croaker (3.77 g per 100 g fatty acids) (Zhao et al . ), which was higher than that in yellow catfish (2.5 g per 100 g fatty acids) (Tan et al . ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…) and large yellow croaker (3.77 g per 100 g fatty acids) (Zhao et al . ), which was higher than that in yellow catfish (2.5 g per 100 g fatty acids) (Tan et al . ).…”
Section: Discussionmentioning
confidence: 69%
“…At the biochemical level, several studies have been conducted to determine the effect of dietary CLA levels on several hepatic lipogenic enzyme activities in fish (Figueiredo‐Silva, Rema, Bandarra, Nunes & Valente ; Valente et al . ,b; Zhao, Wu, Tang & Zhang ). These studies suggested that the effect of CLA on growth performance and hepatic lipogenic enzyme activites was dependent on the species and may possibly be related to the various nutritional and physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Serum IgM and LSZ were enhanced markedly with the increase in dietary CLA, the significant increase in serum LSZ activity indicated that dietary CLA could enhance the antimicrobial defense capability of fish by promoting the activation of phagocytic cells (Makol et al., ; Zhao, Wu & Tang, ). Montero, Tott, Izquierdo, Robaina and Vergara () considered that ACP had a very important role in the non‐specific immunity of fish due to its earlier appearance than immunoglobulin in fish immune system, the promotion of serum ACP in this study further proved the improved immune resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Liver triglyceride concentrations were significantly higher and muscle triglyceride concentrations were lower in fish fed CLA. Hepatic fatty acyl desaturase and elongase mRNA levels in fish fed CLA were lower than in controls (Diez et al 2007) Atlantic cod (Gadus morhua) 0, 0.5 and 1% CLA in juveniles Proximate composition was not affected, and no major effects of either functional fatty acid on lipid contents and compositions of liver and flesh were observed (Kennedy et al 2007b) Channel catfish (Ictalurus punctatus) 0, 0.5 and 1% CLA in juveniles Proximate composition was not significantly affected by CLA (Twibell & Wilson 2003) 0, 0.5 and 1% CLA in juveniles Fillet n)3 HUFA levels were significantly higher for fish fed diets containing fish oil when compared to n)3 HUFA of fillets of fish fed diets containing either corn oil or CLA and corn oil (Manning et al 2006) Hybrid strip bass 0 and 1% CLA in juveniles Total liver lipid concentrations were significantly reduced in fish fed the diets containing CLA, and intraperitoneal fat ratio was significantly lower in fish fed 1.0% CLA compared with fish fed no CLA Feeding CLA resulted in a significant increase in EPA and DHA in liver, but a reduction in muscle (Twibell et al 2000) Yellow Perch (Perca flavescens) 0, 0.5 and 1% CLA in juveniles No effect on muscle proximate composition, but it reduced lipid content and changed fatty acid profile in the liver (Twibell et al 2001) Large yellow croaker (Pseudosciaena crocea) 0, 2 and 4% CLA in adults Muscle lipid significantly reduced with a consequent increase in lean body mass (Sang et al 2007) 0, 1, 2 and 4% CLA in juveniles CLA had no effect on whole body proximate, but showed some significant effects on the fatty acid composition in both muscle and the liver (Zhao et al 2008) R. Rosa et al…”
Section: Fatty Acid Compositionmentioning
confidence: 99%